Targeting IgG Autoantibodies for Improved Cytotoxicity of Bactericidal Permeability Increasing Protein in Cystic Fibrosis - McQuillan, Karen; Gargoum, Fatma; Murphy, Mark P.; McElvaney, Oliver J.; McElvaney, Noel G.; Reeves, Emer P. (Frontiers in Pharmacology, 2020)
In people with cystic fibrosis (PWCF), inflammation with concurrent infection occurs from a young age and significantly influences lung disease progression. Studies indicate that neutrophils are important effector cells in the pathogenesis of CF and in the development of anti-neutrophil cytoplasmic autoantibodies (ANCA). ANCA specific for bactericidal permeability increasing protein (BPI-ANCA) are detected in patients with CF, and correlate with infection with Pseudomonas aeruginosa. The aim of this study was to determine the signalling mechanism leading to increased BPI release by CF neutrophils, whilst identifying IgG class BPI-ANCA in CF airways samples as the cause for impaired antimicrobial activity of BPI against P. aeruginosa. Plasma and/or bronchoalveolar lavage fluid (BAL) was collected from PWCF (n = 40), CF receiving ivacaftor therapy (n = 10), non-CF patient cohorts (n = 7) and healthy controls (n = 38). Plasma and BAL BPI and BPI-ANCA were measured by ELISA and GTP-bound Rac2 detected using an in vitro assay. The antibacterial effect of all treatments tested was determined by colony forming units enumeration. Levels of BPI are significantly increased in plasma (p = 0.007) and BALF (p < 0.0001) of PWCF. The signalling mechanism leading to increased degranulation and exocytosis of BPI by CF neutrophils (p = 0.02) involved enhancement of Rac2 GTP-loading (p = 0.03). The full-length BPI protein was detectable in all CF BAL samples and patients displayed ANCA with BPI specificity. IgG class autoantibodies were purified from CF BAL complexed to BPI (n=5), with IgG autoantibody cross-linking of antigen preventing BPI induced P. aeruginosa killing (p < 0.0001). Results indicate that the immune-mediated diminished antimicrobial defence, attributed to anti-BPI-IgG, necessitates the formation of a drug/ immune complex intermediate that can maintain cytotoxic effects of BPI towards Gram-negative pathogens, with the potential to transform the current treatment of CF airways disease.